Thermodynamik von Kobaltoxid Anodenmaterialien für Lithium-Ionen-Batterien und ihr elektrochemisches Verhalten - Mayer, Nicolas A. (Schriftenreihe des Instituts fur Angewandte Materialien, Karlsruher Institut fur Technologie, 2020)
A thermodynamic approach is used to gain new insights into reaction mechanism and correlations between electrochemical and thermodynamic properties of conversion electrodes in the material system Li-Co-O. For this purpose, thermodynamic modeling using the CALPHAD method as well as measurements of the thermodynamic and electrochemical properties of the electrode materials were performed.